PERAN ORANG TUA TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI DI TK ISLAM PRAJAMUDA - Siti aisyah siti aisyah; Nihwan nihwan nihwan (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2023)
The family environment is the initial environment of the child, all the behavior and development of the child is imitated by both parents. If parents are able to set a good example and role model for their children, then the child's attitude is not much different from that of the parents. Vice versa, if parents cannot be a good example, parents cannot expect their children to be better and fulfill the wishes of their parents. Based on the background described above, the formulation of the problem can be concluded in this research, namely: "What is the role of parents on social emotional development of early childhood in PRAJAMUDA ISLAMIC KINDERGARTEN.” using qualitative methods, data were collected by collecting data in the form of interviews, observation and documentation. This research focuses on the role of parents in the social-emotional development of early childhood in the Prajamuda Islamic Kindergarten. Data collection techniques carried out in the form of interviews, observations conducted by researchers at PRAJAMUDA ISLAMIC Kindergarten. The process of data analysis was carried out by displaying data, data reduction, and drawing conclusions. The role of parents as a control over children's social development, b. The role of parents in giving attention as a child's emotional development, c. The role of parents as a motivator can be concluded that the role of parents in the social emotional development of early childhood has 3 roles, namely: the role of parents as a control over children's social development, the role of parents in giving attention as a child's emotional development, the role of parents as a motivator.